A Multicenter, Open-Label, Controlled Phase II Study to Evaluate Safety and Immunogenicity of MVA Smallpox Vaccine (IMVAMUNE) in 18–40 Year Old Subjects with Diagnosed Atopic Dermatitis - Greenberg, Richard N; Hurley, Yadira; Dinh, Dinh V.; Mraz, Serena; Vera, Javier Gomez; von Bredow, Dorothea; von Krempelhuber, Alfred; Roesch, Siegfried; Virgin, Garth; Arndtz-Wiedemann, Nathaly; Meyer, Thomas Peter; Schmidt, Darja; et al. (PloS one, 2015)
Replicating smallpox vaccines can cause severe complications in individuals with atopic dermatitis (AD). Prior studies evaluating Modified Vaccinia Ankara virus (MVA), a non-replicating vaccine in humans, showed a favorable safety and immunogenicity profile in healthy volunteers. This Phase II study compared the safety and immunogenicity of MVA enrolling groups of 350 subjects with AD (SCORAD ≤ 30) and 282 healthy subjects. Subjects were vaccinated twice with MVA, each dose given subcutaneously 4 weeks apart. Adverse events, cardiac parameters, and the development of vaccinia virus humoral immune responses were monitored. The overall safety of the vaccine was similar in both groups. Adverse events affecting skin were experienced significantly more often in subjects with AD, but the majority of these events were mild to moderate in intensity. Seroconversion rates and geometric mean titers for total and neutralizing vaccinia-specific antibodies in the AD group were non-inferior compared to the healthy subjects. The size of the study population limited the detection of serious adverse events occurring at a frequency less than 1%. MVA has a favorable safety profile and the ability to elicit vaccinia-specific immune responses in subjects with AD. ClinicalTrials.gov NCT00316602.